Association of Glycosylated Hemoglobin A1c Level With Sudden Sensorineural Hearing Loss: A Prospective Study - Shen, Ying; Zheng, Zhong; Xiao, Lili; Liu, Chengqi; Guo, Jingyi; Chen, Zhengnong; Wu, Yaqin; Shi, Haibo; Zhang, Zhen; Qian, Di; Feng, Yanmei; Yin, Shankai (Frontiers in Endocrinology, 2021)
Glycosylated hemoglobin A1c (HbA1c) level has strong relevance to microvascular disorders, which are also thought to be the current main aspect of sudden sensorineural hearing loss (SSNHL). So, we aim to elucidate the association of the HbA1c level with the severity, types and prognosis of SSNHL. In this study, comparative analyses based on propensity score matching of the severity, types and prognosis of SSNHL with the HbA1c level in 116 patients diagnosed as SSNHL were conducted, where they were divided into diabetes mellitus (DM) group and non-DM group. We finally found that among patients with SSNHL, diabetic patients had higher HbA1c level, more severe hearing loss and poorer prognosis than non-diabetic patients. The HbA1c level was found to be significantly correlated with the severity and types of SSNHL. While, no strong relevance was found between the higher HbA1c level and the poorer prognosis of SSNHL.